Use of kaolin as adsorbent for removal of hydrogen sulphide from biogas - Abdullah, A. H. (Italian Association of Chemical Engineering - AIDIC, 2017)
Biogas desulphurisation needs to be done before being used as the alternative energy sources of fuel. Presently, biogas desulphurisation through the adsorption process is an attractive method due to its simple process and low starting cost. Currently available adsorbent such as activated carbon, metal/metal oxide and zeolite are the key factor for effective biogas desulphurisation by adsorption process. Utilisation of biogas as alternative fuel is not feasible due to presences of hydrogen sulphide. This factor is the main reason to the slow commercialisation of biogas fuel. Introduce of less expensive but high efficiency method for biogas upgrading process will help to overcome this problem. Low cost biogas upgrading process can be established by using low cost adsorbent material which is the main cost associated with biogas purification. Malaysia has large amount deposit of kaolin. Kaolin deposit can be found in states of Perak, Johor, Kelantan, Selangor, Pahang and Sarawak. The present of metal oxides in kaolin makes it possible to be used as H2S adsorbent. The present work was undertaken to investigate the feasibility of using kaolin for H2S removal by adsorption. Dynamic tests were carried out at room temperature to evaluate the capacities of the sorbents for H2S removal using fixed bed reactor. Several reaction parameters such H2S inlet flowrate, and reaction temperature that affect breakthrough adsorption capacity were studied. Kaolin sample was characterised using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and X-ray fluorescence (XRF). The results show that kaolin was able to remove low amount H2S. Further modification is needed to improve its performance.